Disfuncionalidad familiar y conductas antisociales en adolescentes de la Unidad Educativa “Juan de Velasco”, Riobamba, periodo 2017- 2018 - Paz Enríquez, Evelyn Dayana (2018)
This investigation starts from the variables, family dysfunctionality and anti-social behaviors in a sample of 129 adolescents who study at Educational Unit "Juan de Velasco" from Riobamba. The objective: Determine family dysfunctionality and anti-social behaviors. Quantitative study, transversal, field study, no experimental and descriptive, using psychological tests examples: Family Apgar questionnaire by Smilkstein and the Antisocial Conduct Questionnaire by Martorell y González. Results obtained: Regarding to family dysfunction the 49% of adolescents integrated family systems with a moderate level of dysfunction, 37% integrated family systems with a mild level of dysfunction, 11% are part of a normal range and, 3% integrated family systems with a severe level of dysfunction. Concerning the anti-social behavior, the 86% have a moderate risk of antisocial behavior, 9% have a low risk of anti-social behavior and 5% have a high risk of anti-social behavior. Concluding that adolescents present a high risk of antisocial behavior, with a higher tendency in male adolescents and a lower tendency in women; likewise, greater aggressiveness in men and greater isolation in women. In the research the statistical package used was SPSS 24.0, which it was determined that there is a highly significant correlation between the level of family dysfunctionality and anti-social behaviors, directly proportional. Evidence from the study, the greater the family dysfunction, the greater the risk of antisocial behavior.